2009
DOI: 10.1002/jrs.2228
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman scattering influenced by concentration, fluorescence profile and bandwidth of β‐carotene in liquid‐core optical fiber

Abstract: We demonstrated stimulated Raman scattering (SRS) of carbon disulfide (CS 2 ) influenced by β-carotene in a liquid-core optical fiber (LCOF). Owing to the double fluorescence characteristics and large third-order optical nonlinearity of β-carotene, the high-order Stokes lines, such as the seventh-order Stokes line of CS 2 , can be observed at a relatively low input-laser power. The thresholds of Stokes lines lowered with the addition of the carotenoid when the concentration of solution was within 10 −12 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The facture of the LCOF is shown by previous papers [19][20][21]. The experimental setup is shown elsewhere [13].…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The facture of the LCOF is shown by previous papers [19][20][21]. The experimental setup is shown elsewhere [13].…”
Section: Methodsmentioning
confidence: 98%
“…In order to lower the threshold of SRS and enhance the intensity of SRS, some methods are applied, such as fluorescent dyes to enhance the SRS [7], micrometer-sized droplets to enhance the SRS [8,9], liquid-core optical fibers (LCOFs) to enhance the SRS [10], intramolecular Fermi resonance to enhance the SRS [11] and so on. The fluorescent dye enhancement to SRS in a LCOF has been investigated by our team in the last few years [12,13]. But the intermolecular Fermi resonance to enhance the SRS has not been researched as far as we know.…”
Section: Raman Lasers and Raman Amplifiersmentioning
confidence: 98%
“…[16] The experimental setup is given elsewhere. [17] For excitation, two semiconductor lasers were used that emit at 658 and 532 nm. The laser power was in a range of 0-1 W and 0-30 mW, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Lorono et al [138] reported high-resolution SRS and analysis of the overtone symmetric motion of C 2 H 4 . Men et al [139] showed that the SRS of CS 2 is influenced by β-carotene in a liquid-core optical fiber. Their results are expected to be useful for applications involving tunable as well as seeding lasers.…”
Section: Stimulated Raman Spectroscopymentioning
confidence: 99%